The Public Value of E-government: A Qualitative Study from the Perspective of Private-Sector Professionals in Morocco - Chaimaa, Idaomar; Khalid, Chafik (European Scientific Journal, ESJ, 2024)
This paper focuses on assessing the public value of e-government in Morocco, using Delone and Mclean’s (2016) Information Systems (IS) success model as a reference framework. The methodology is based on a qualitative exploratory study involving 13 companies, including law firms, architecture firms, and real estate developers firms. An interview guide was designed to collect data, which were analyzed using Nvivo Qsr 12 software. The analysis identified six variables, namely: "Human Capital, Telecommunication Infrastructure, Willingness to Use, State Strategy, Continuous Education, and Culture," which were added to the seven predetermined variables of the Delone and Mclean (2016) IS Success Model. This research outlines practical implications that are essential for the long-term success of e-government initiatives in Morocco. These include investing in skills development, effectively communicating the benefits of e-government, promoting collaboration between the public and private sectors, recognizing organizational culture, putting mechanisms in place to measure performance and user satisfaction, as well as making adjustments to organizational processes and rigorously managing data security. On a political level, these adjustments underline the importance of a coherent government strategy, which focuses on strengthening human capital and telecommunications infrastructures, in order to promote a successful digital transformation and achieve the objectives of trust, transparency, and efficiency in public services.